1995
DOI: 10.1183/09031936.95.08071155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of children with chronic respiratory symptoms in eastern Finland

Abstract: P Pr re ev va al le en nc ce e a an nd d c ch ha ar ra ac ct te er ri is st ti ic cs s o of f c ch hi il ld dr re en n w wi it th h c ch hr ro on ni ic c r re es sp pi ir ra at to or ry y s sy ym mp pt to om ms s i in n e ea as st te er rn n F Fi in nl la an nd d ABSTRACT: The objective of the present study was to assess the prevalence of asthma and asthma-related symptoms in Finland. We also wondered whether chronic cough may be an indicator of occult asthma. Prevalence and characteristics of children with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 36 publications
7
63
4
Order By: Relevance
“…Recently, a prevalence of 4.4% of doctor-diagnosed asthma was reported among children aged 7-12 yrs in Kuopio, East Finland [6,19], which is consistent with the present results. In Turku, a prevalence of 2.5% of doctor-diagnosed asthma was recently reported among adolescents [16]; which was less than half of that in the present study (7%).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a prevalence of 4.4% of doctor-diagnosed asthma was reported among children aged 7-12 yrs in Kuopio, East Finland [6,19], which is consistent with the present results. In Turku, a prevalence of 2.5% of doctor-diagnosed asthma was recently reported among adolescents [16]; which was less than half of that in the present study (7%).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of asthma and wheezing was relatively low in comparison with figures reported recently in Europe. However, another Finnish study 6 of children aged 7 to 12 years reported prevalences of 4.4% for doctor-diagnosed asthma and 5.4% for wheezing during the previous 12 months, figures that correspond to those of the present study when the slightly higher age range is taken into account.…”
Section: Resultssupporting
confidence: 88%
“…5 That research suggested that minimizing financial barriers to mammography screening does not necessarily ensure high rates of use. 6,7 There were several limitations to our study, however. First, the comparison between the United States and Canada was restricted to Ontario.…”
Section: Contributorsmentioning
confidence: 89%
See 1 more Smart Citation
“…The population characteristics are fairly typical of young individuals with well-controlled asthma derived from both primary and secondary care (Table 1) (21). Figure 1A shows the proportion of population on various stages of management as per BTS guidelines with asthma exacerbations over the previous 6 months.…”
Section: Resultsmentioning
confidence: 99%